Short-term effect of internet-delivered mindfulness-based stress reduction on mental health, self-efficacy, and body image among women with breast cancer during the COVID-19 pandemic - Chang, Yun-Chen; Chiu, Chang-Fang; Wang, Chih-Kai; Wu, Chen-Teng; Liu, Liang-Chih; Wu, Yao-Chung (Frontiers in Psychology, 2022)
Background and Aim: During the COVID-19 pandemic, an Internet-Mindfulness-Based Stress Reduction (iMBSR) program was delivered and may be better than an in-person approach. Our study evaluated the effects of iMBSR intervention on mental health, self-efficacy, and body image in women with breast cancer in Taiwan. Materials and Methods: Sixty-seven women with breast cancer were allocated to a 6-week iMBSR (n = 41) program or a waitlist control group (n = 26), without heterogeneity between group characteristics. Patients from both groups were measured at baseline and postintervention using three scales: Depression, Anxiety, and Stress Scale (DASS-21), General self-efficacy scale, and Body Image Scale. Descriptive dataset analysis, paired t test, and Student’s t test were used to evaluate the data. Results: Although iMBSR did not significantly improve depression and stress between groups, iMBSR could improve anxiety (Δmean: -2.0 vs. -0.4, p =0.041) with medium effect sizes. Significant benefits were found for body image (Δmean: -3.6 vs. 0.9, p = .003) and self-efficacy (Δmean: 4.2 vs. 1.5, p = .004), with large effect sizes (Cohen's d = .73). Conclusion: Our preliminary study supports iMBSR as a program that can improve mental health, body image, and self-efficacy in women with breast cancer. During the COVID-19 pandemic, medical professionals can use Internet-based clinical health education.